Menganalisis Peran Konten Video Sebagai Alat Utama Dalam Media Promosi Produk Untuk Meningkatkan Konsumen Dan Keberhasilan Branding - Athoillah, Naufal Athoillah; Pungky Febi Arifianto (Lembaga Pengembangan Kinerja Dosen, 2024)
This study reviews the crucial role of video content as the main tool in product promotion media with the aim of increasing consumer engagement and branding success. Through in-depth analysis of marketing strategies that use video content, this research identifies the positive impact of video content on consumer engagement levels, building emotional connections, and increasing brand awareness. The factors of creativity, authenticity and understanding the target market are also considered important elements in the success of a promotional campaign. The practical implications of this research provide valuable guidance for marketing practitioners to optimize the role of video content in achieving branding goals and increasing consumer appeal.